Gut Microbiota-Mediated Modulation of Cancer Progression and Therapy Efficacy - Cheng, Peng; Shen, Peiliang; Shan, Yunlong; Yang, Yu; Deng, Rui; Chen, Wenxing; Lu, Yin; Wei, Zhonghong (Frontiers in Cell and Developmental Biology, 2021)
The role of gut microbiota in the development of various tumors has been a rising topic of public interest, and in recent years, many studies have reported a close relationship between microbial groups and tumor development. Gut microbiota play a role in host metabolism, and the positive and negative alterations of these microbiota have an effect on tumor treatment. The microbial groups directly promote, eliminate, and coordinate the efficacy of chemotherapy drugs and the toxicity of adjuvant drugs, and enhance the ability of patients to respond to tumors in adjuvant immunotherapy. In this review, we outline the significance of gut microbiota in tumor development, reveal its impacts on chemotherapy and immunotherapy, and discover various potential mechanisms whereby they influence tumor treatment. This review demonstrates the importance of intestinal microbiota-related research for clinical tumor treatment and provides additional ideas for clinical assistance in cancer treatment.